Transformasi Karakter Religius Santri Melalui Halaqah Tarbiyah: Analisis Peran Murabbi dan Internalisasi Nilai 5M Wahdah Islamiyah di Pesantren Tahfidz: Transforming Religious Character through Halakah Tarbiyah: The Role of Murabbi and the Implementation of the 5M - Iskandar; Samsuddin; Abdul Jabar Idharudin; Balkis Nur Azizah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to analyze the role of the murabbi (spiritual mentor) in the process of transforming students’ religious character through halakah tarbiyah activities and to examine the internalization of the 5M values (mukmin, mushlih, mujahid, mutqin, and muta’awin) at the Wahdah Islamiyah Cibinong Tahfidz Islamic Boarding School. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data were analyzed in three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that halakah tarbiyah functions as the main instrument for character formation through a process of structured spiritual guidance and collective religious practices. The murabbi plays a central role as a facilitator, role model, and motivator in instilling Islamic values. The internalization of the 5M values is carried out gradually through halakah sessions, mentoring, and daily evaluations. These values have proven effective in fostering students’ religious awareness, moral responsibility, and worship discipline. The contribution of this study lies in strengthening a tarbiyah-based character education model that is relevant to the development of Islamic formation systems in modern Islamic boarding schools.